Local open government: Key issues in Contagem, Brazil - Afandi, Syed Agung; Erdayani, Rizki (Priviet Social Sciences Journal, 2026)
This study aims to analyze the key issues of open government in Contagem, Brazil, using a bibliometric analysis approach. Research data were collected from Google Scholar using Publish or Perish and analyzed with VOSviewer through co-occurrence techniques on keyword units with the full counting method. The findings revealed three major dimensions within the discourse: normative, policy, and local practice. The normative dimension underscores transparency and accountability in digital platforms. The policy dimension demonstrates the institutionalization of open government principles in urban planning and social programs. The local practice dimension reflects contextual adaptation by emphasizing inclusivity, sustainability, and smart governance. Moreover, the five core commitments of Contagem—digital participation through Decidim, the Integrity Plan, the establishment of CPRAC-C for administrative conflict resolution, a mobile application for georeferencing third-sector services, and the enhancement of the Transparency Portal—illustrate the city’s serious efforts to integrate OGP values at the local level. Nevertheless, several challenges remain, including limited and uneven citizen engagement, fragmentation of participatory instruments, digital divides, and the risk of symbolic implementation of the law. This study concludes that Contagem represents both opportunities and constraints in the execution of local open government, underscoring the need to strengthen inclusiveness, operational integrity, and integration of participatory mechanisms. Reinforcing these aspects would not only consolidate Contagem’s position within Brazil, but also enable it to serve as a model for participatory and sustainable urban governance in Latin America.